Absorption Resonance Energy Transfer between Organic Dyes (Cumarin and Rohdamain ) - Wajeha Abdle Diam (Journal of Global Pharma Technology, 2016)
The spectral properties absorption of two laser dyes types, C480 and R610, the mixture was investigated. These types of laser dyes belong to Coumarinoids and Xanthenes family were dissolved using ethanol as solvent to prepare samples with range of ratios (1:1, 1:2, 1:3 and 1:4) from Cumarin 480 (C48) to Rohdamin 610 (R610) concentered in (10-410-5,10-6) M/L at room temperature. The achieved results pointed out an increase in the absorption intensities with the increasing of the concentration of the day type R610 from 10-6 and 10-5 to 10-4 M/L.the same thing for C480which are absorved in agreement with Beer-Lambert law and the finished results Pointed that the absorption peak was moved toward the short wavelengths (BLUE SHIFT) when increasing the ratioconcentration. Keywords: Dye laser, Fluorescence resonance energy transfer, Silica gel matrices. Absorption spectrum.